Implementation of Project Based Learning (PJBL) Model with the Assistance of Media E-Learning Chamilo to Improve Student's Understanding of Physics Concepts - Mukhammad Nur Chasani; Agung Suci Dian Sari (SAGA: Journal of Technology and Information System, 2023)
This study aims to: (1) produce physics learning by using Project Based Learning (PjBL) with the assistance of E lerning Chamilo media that is appropriate to increase students' understanding of physics concepts during a pandemic, (2) to find out how high the understanding of physics concepts is by using learning Project Based Learning (PjBL) Assisted by Media E Lerning Chamilo, (3) find out how high the understanding of students' concept understanding in learning physics is increased by using the Project Based Learning (PjBL) learning model assisted by E Lerning Chamilo's media. The subjects in this study were 108 students of SMA Negeri 1 Kejayan Class MIA 4, MIA 5 and MIA 6. This study uses the Project Based Learning (PjBL) method assisted by Media E Lerning Chamilo. Defining is the initial stage of developing learning based on task analysis and concept analysis. Design is the second stage of the development of this learning which aims to produce an initial design of thE-Learning to be developed. The next stage is development which consists of testing the first stage including validation from the validator. the second stage of testing, namely the trial phase includes student responses to learning, along with giving interest questionnaires and also pretest and posttest questions. The data analysis technique used to analyze each data is the conversion of quantitative to qualitative values for the validation of Project Based Learning (PjBL) learning assisted by the E Lerning Chamilo media and the conversion of quantitative to qualitative values and normalized gain for interest data and student tests. The results of the development of this media show that: 1) E Lerning Chamilo based physics learning media is suitable for use as a physics learning medium with the subject of momentum, impulse, and collision. 2) the use of Project Based Learning (PjBL) learning media assisted by E Lerning Chamilo media can increase students with a gain value of 4.10 (high category).